Mechanical, dielectric, and thermal properties of polydimethylsiloxane/polysilsesquioxane nanocomposite for sealant application. Issue 12 (23rd November 2018) - Anoop, V.; Subramani, S.; Jaisankar, S. N.; Sohini, C.; Mary, N. L.
ABSTRACT: Polysilsesquioxanes (PS) powder was synthesized from methyltrimethoxysilane and vinyltrimethoxysilane by hydrolytic condensation method in aqueous phase. The prepared PS powder was characterized using Fourier transform infrared spectroscopy, particle size, and polydispersity of the powders was determined using dynamic light scattering technique. Polydimethylsiloxane (PDMS) nanocomposites and the sealant were synthesized using different weight percentage (1–4 wt %) of PS powder and hydrophobic fumed silica. Tensile strength and thermal stability of the nanocomposites showed perceptible enhancement on increasing the filler ratio when compared to pristine PDMS composites. The surface morphology and the extent of filler dispersion were visualized from the scanning electron microscopy images. Dielectric strength of the composites also showed significant improvement on increasing the filler loading. Poly(methyl/vinyl)silsesquioxane (PMVS) (4 wt %) reinforced composites showed a considerable enrichment in properties when compared to other formulations. Adhesive strength of silicone sealant on both the alumina and mild steel substrate was studied by conducting lap shear test. PMVS‐loaded nanocomposites exhibited more adhesive strength on both the substrates and hence it can be used as a sealant in electronic assemblies. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47228. Abstract :